Hypoxia-adenosine axis as therapeutic targets for acute respiratory distress syndrome - Figarella, Katherine; Kim, Jieun; Ruan, Wei; Mills, Tingting; Eltzschig, Holger Klaus; Yuan, Xiaoyi (Frontiers in Immunology, 2024)
The human respiratory and circulatory systems collaborate intricately to ensure oxygen delivery to all cells, which is vital for ATP production and maintaining physiological functions and structures. During limited oxygen availability, hypoxia-inducible factors (HIFs) are stabilized and play a fundamental role in maintaining cellular processes for hypoxia adaptation. First discovered during investigations of erythropoietin production regulation, HIFs influence physiological and pathological processes, including development, inflammation, wound healing, and cancer. HIFs promote extracellular adenosine signaling by enhancing adenosine generation and receptor signaling, representing an endogenous feedback mechanism that curbs excessive inflammation, supports injury resolution, and enhances hypoxia tolerance. This is especially important for conditions that involve tissue hypoxia, such as acute respiratory distress syndrome (ARDS), which globally poses significant health challenges without specific treatment options.Consequently, pharmacological strategies to amplify HIF-mediated adenosine production and receptor signaling are of great importance.